(untitled) (Journal of Science and Technology, 2016)
Annealed and non-annealed freeze-dried wafers from synthesised thiolated-chitosan have been developed and evaluated. Wafers were obtained by freeze-drying aqueous gels of the thiolated polymer incorporating per polymer weight, 10 % each of glycerol as plasticizer, D-mannitol as cryoprotectant and 50% BSA as model protein drug. The formulation was freeze-dried with or without the process of annealing. Texture analyzer was employed to investigate the in vitro mucoadhesive properties in tensile mode, residual moisture content by thermo-gravimetric analysis (TGA) while hydration capacity and drug release studies were performed in 0.1M PBS. Microscopic architecture was examined using scanning electron microscopy (SEM). Differential scanning calorimetry (DSC) was employed for protein phase separation studies and conformational stability by attenuated total reflectance-Fourier transform infra-red spectroscopy (ATR-FTIR) and confirmed with Circular dichroism (CD). The annealing process led to wafers with increased ease of hydration, improved in vitro mucoadhesive characteristics and enhanced BSA release, without affecting the conformational stability of the protein due to the presence of a cryoprotectant. These results show the potential application of annealed freeze-dried thiolatedchitosan wafers for buccal mucosa delivery of protein based drugs.